A guide to treating Ironman triathletes at the finish line - Mayers, L. B.; Noakes, T. D. (The Physician and Sportsmedicine, 2000)
The unique physiologic characteristics of an ironman triathlete present challenges to physicians covering ultraendurance events. Cardiovascular emergencies at the finish line are rare. Occult blood in postrace urine is common but rarely of clinical significance. Medical volunteers must distinguish between signs of dehydration, heatstroke, hyponatremia, and postural hypotension and offer appropriate treatment. Recumbent positioning and oral hydration often suffice to stabilize a conscious collapsed athlete, but serious abnormalities require swift evacuation to a hospital.